2021
DOI: 10.1097/cm9.0000000000001393
|View full text |Cite
|
Sign up to set email alerts
|

Olecranon osteotomy vs. triceps-sparing for open reduction and internal fixation in treatment of distal humerus intercondylar fracture: a systematic review and meta-analysis

Abstract: Background The open reduction and internal fixation (ORIF) was a standard treatment approach for fracture at distal humerus intercondylar, whereas the optimal way before ORIF remains inconclusive. We, therefore, performed a systematic review and meta-analysis to assess the efficacy and safety of olecranon osteotomy vs . triceps-sparing approach for patients with distal humerus intercondylar fracture. Methods The electronic searches were system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Radiological outcome revealed that, union achieved in all patients. The mean time of bone union was 14.8 ± 0.72 weeks [12][13][14][15][16][17][18][19][20]. There were no non-union.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Radiological outcome revealed that, union achieved in all patients. The mean time of bone union was 14.8 ± 0.72 weeks [12][13][14][15][16][17][18][19][20]. There were no non-union.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, ORIF was applied for 33 patients with distal humerus fractures through triceps-sparing approach. The mean elbow flexion was 140.45±3.82 degrees [135-145], and the mean elbow extension was 9.96±2.98 degrees [6][7][8][9][10][11][12][13][14][15]. Radiological outcome was achieved in all patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] The application of this approach in the treatment of distal humerus fractures has been reported in several studies, [9][10][11] including systematic reviews that have compared triceps-sparing approach with OO. [12] The paratricipital approach (PT), introduced by Alonso-Llames in 1972 [13] for the treatment of supracondylar fractures in children and modified by Schildhauser et al [14] for exposure of the articular surface of the distal humerus, has been investigated relatively recently. This approach offers the advantage of sparing the insertion of the triceps, which results in preservation of the extensor mechanism, when compared with other approaches.…”
Section: Introductionmentioning
confidence: 99%
“…[8] The application of this approach in the treatment of distal humerus fractures has been reported in several studies, [9–11] including systematic reviews that have compared triceps-sparing approach with OO. [12]…”
Section: Introductionmentioning
confidence: 99%